2019
DOI: 10.1111/vcp.12771
|View full text |Cite
|
Sign up to set email alerts
|

The utility of diagnostic tests for immune‐mediated hemolytic anemia

Abstract: Background:A definitive diagnosis of immune-mediated hemolytic anemia (IMHA) can be difficult to make. However, it is critical to differentiate IMHA from other causes of anemia due to the impact on prognosis and outcome for IMHA patients. Recently published American College of Veterinary Internal Medicine recommendations for the diagnosis of IMHA should be followed to concurrently confirm ongoing anemia, verify in vivo hemolysis, and detect anti-erythrocyte antibodies. The reliability of immunologic IMHA tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…In 2019, the American College of Veterinary Internal Medicine (ACVIM) consensus statement offered similar guidelines, but the data substantiating these recommendations were sparse [ 6 ]. There remain disparities regarding the routinely used diagnostic techniques and interpretations of specific test results for diagnosis of IMHA in veterinary clinics as well as in laboratories, as recently illustrated in a small survey by the Veterinary and Comparative Clinical Immunology Society [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, the American College of Veterinary Internal Medicine (ACVIM) consensus statement offered similar guidelines, but the data substantiating these recommendations were sparse [ 6 ]. There remain disparities regarding the routinely used diagnostic techniques and interpretations of specific test results for diagnosis of IMHA in veterinary clinics as well as in laboratories, as recently illustrated in a small survey by the Veterinary and Comparative Clinical Immunology Society [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in a recent study of dogs suspected of having IMHA, only 20% were tested by DAT [ 19 ]. As such, a presumptive diagnosis of IMHA is frequently made without evidence of immune-mediated destruction of erythrocytes in anemic dogs [ 1 – 3 , 7 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is because the role of glucocorticoids in the disease is to reduce the production of red blood cell antibodies and prolong the life of red blood cells (Oggier et al 2018). It has been reported that the autocoagulation reaction of normal saline can be used to make a preliminary diagnosis, and the suspected immune-mediated hemolysis can be further confirmed by direct Coomb's test (MacNeill et al 2019). Due to our inexperience at the beginning of the treatment, this was not confirmed by the Coombs test.…”
Section: Discussionmentioning
confidence: 92%
“…The indirect antiglobulin (Coombs’) test (IAT) is routinely used in human medicine for the detection of anti-erythrocytic allo- and autoantibodies in plasma and serum to ensure blood transfusion compatibility or to diagnose IMHA, respectively [ 15 , 39 ]. In contrast, little is known about the value of IAT in diagnosing dogs and other domestic animal species suspected of having IMHA [ 17 , 18 ]. When using currently available canine antiglobulin reagents with different in-clinic and laboratory immunodiagnostic techniques to detect anti-erythrocytic autoantibodies in 94 serum samples from DAT+ and DAT− dogs, we show here that the various IAT methods are specific, but less sensitive analytical diagnostic tools to detect anti-erythrocytic autoantibodies compared to the equivalent DAT techniques reported by us recently [ 10 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the potential value of the IAT in the diagnosis of IHMA dogs [ 17 , 18 ] is relatively unexplored. Indeed, the use of IAT to diagnose IMHA dogs in clinical practice is quite rare [ 18 ], presumably due to the fear of interfering with alloantibodies giving false positive results [ 19 , 20 , 21 ]. However, such concerns appear unwarranted, as dogs have no clinically important alloantibodies prior to being transfused [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%